Comparison of central and peripheral corneal thickness measurements with scanning-slit, Scheimpflug and Fourier-domain ocular coherence tomography. Issue 9 (30th March 2015) - Randleman, J Bradley; Lynn, Michael J; Perez-Straziota, Claudia E; Weissman, Heather M; Kim, Sang Woo
Abstract : Purpose: To compare central, regional and relational corneal thickness values obtained with multiple technologies in normal patients and to determine their equivalence and interchangeability. Methods: Retrospective analysis of 100 eyes from 50 patients evaluated by ultrasound pachymetry (Pachette II), scanning-slit (Orbscan II), Scheimpflug (Pentacam HR) and spectral-domain ocular coherence tomography (OCT) (RTVue-100) obtained as average values (OCT-A) and point measurements (OCT-P). Measurements included central corneal thickness (CCT) for all technologies and thinnest corneal thickness for scanning-slit, Scheimpflug and OCT. Peripheral thickness measurements were obtained at the 3 mm radius in the superior (S), nasal (N), inferior (I) and temporal (T) regions. Results: CCT values were: 563.9±36.1μ ultrasound, 570.9±36.1μ scanning-slit, 552.8±33.8μ Scheimpflug, 550.5±32.7μ (OCT-A), 549.4±32.7μ (OCT-P). Ultrasound and scanning-slit were significantly different from each other (p<0.0001), and both were significantly different from all other devices (p<0.0001), while Scheimpflug was similar to OCT-A and OCT-P (p=0.4). Differences between CCT and thinnest corneal thickness were significantly different from all technologies except scanning-slit and OCT-A. For peripheral values, almost all locations' measurements were significantly different from one another (p<0.0001). Superior–inferior values and ratios were also significantly different from one another for almost all devices with no consistent patterns detectible. Conclusions: There are significant clinically relevant differences between regional and relational thickness measurements obtained with ultrasound, scanning-slit, Scheimpflug and OCT devices. Screening metrics devised for one system do not appear directly applicable to other measurement systems.